Experimental Study on Light Weight Concrete by Partial Replacement of Cement by Flyash, Coarse Aggregate Pumice Stone and Thermocol Beads (International Journal of Innovative Research in Computer Science & Technology, 2022)
In today’s world when focus is on  reducing self-weight of concrete, light weight concrete has  come with the high number of applications to reduce self weight of concrete. In this study an attempt has been made  to compare conventional concrete with the lightweight  concrete which is made by partially replacing cement with  fly ash and coarse aggregate with pumice stone and adding  Thermocol beads using M25 grade of concrete.  Lightweight concrete has been made by partial  replacement of Coarse aggregate by pumice stone varying  in the ratio of 10% 15% and 20% and Thermocol beads by  0.2%, 0.4% and 0.6%.Also cement is replaced by fly ash  in the varying ratios of 20% 30% and 40% by weight of  cement. In addition to that fine aggregate is replaced by  Thermocol beads in the varying ratios of 0.2%, 0.4%and  0.6%.
Keywords: Light weight concrete; Fly Ash; Pumice Stone; Thermocol Beads; Aggregates